Advances in Chip‐Scale Quantum Photonic Technologies. Issue 12 (9th November 2021) - Lu, Liangliang; Zheng, Xiaodong; Lu, Yanqing; Zhu, Shining; Ma, Xiao‐Song
Abstract: Quantum photonic system has made remarkable achievements in computing and communication. Serving as quantum information carriers, photons are flying qubits and robust against decoherence, emerging as a desirable platform to make quantum processor a reality. However, with system's complexity and functionality scaling up, the requirements for stability, programmability, and manufacturability will be in high demand. Integrated photonics, compatible with complementary metal‐oxide‐semiconductor fabrication, has overwhelming dominance in terms of density and performance, making it an unrivaled contender for large‐scale quantum information processing (QIP). To improve the performance of individual blocks and integrate them on a common substrate is one of the core tasks for a practical quantum processor. Here, the recent advances in components that constitute quantum photonic systems on silicon photonics platform, including sources, modulators, and detectors are reviewed. Burgeoning quantum photonics applications, such as multi‐dimensional, multi‐photon QIP and integrated quantum key distribution are highlighted. Abstract : Integrated quantum photonic system, compatible with complementary metal‐oxide‐semiconductor fabrication, has become one of the promising candidates for realizing large‐scale quantum information processing (QIP). In this article, the authors review the recent advances in components that constitute quantum photonic systems including quantum light sources, modulators, and detectors. The richness of these components to explore QIP applications is highlighted.